Foreign Experience In Regulating And Supporting Small Business By The State - Makhmudova Dilbar Rakhmonovna (Genius Journals, 2022)
The article discusses the system of state regulation and support measures to improve the management of small business, analyzes the economic, social and political process. The importance of foreign experience and the views of scientists in the development of the industry in the digital economy has been studied. Practical suggestions and recommendations on the topic have been developed
Keywords: Small Business; Digital Economy; Traditional And Innovative Approaches To Evaluating; Effectiveness